성인 단안 약시 환자에서의 문양시유발전위 검사의 진단적 기준 - 임선희; Sun Hee Lim; 임기환; Key Hwan Lim (Daihan angwa haghoi jabji, 2013)
목적: 성인 단안 약시 환자의 문양시유발전위 검사 결과를 정상군과 비교하여 약시 진단에서의 기준을 제시해보고자 하였다. 대상과 방법: 2000년 1월부터 2011년 12월까지 병사용 진단서 발급을 위해 내원한 성인 약시 환자군과 정상군의 문양시유발전위 검사의 변수(parameters)를 후향적으로 분석하였다. 결과: 단안 약시군은 47명, 정상 대조군은 39명이었다. 약시군에서 문양시유발전위 검사의 변수는 모두 정상군과 통계적으로 유의한 차이를 보였다. 약시 진단시 기준 수치는 ROC 곡선(Receiver Operation Characteristic Curve)을 통해 절단값(cut-off value)을 적용하여, P100 잠복기 113.50 msec, P100 잠복기 비 1.05, P100 잠복기의 양안 차이 8.50 msec, P100 진폭의 양안 차이 5.25 μV였고, 각 민감도는 51.1%, 70.2%, 53.2%, 31.9%로 낮게 측정되었다. 결론: 문양시유발전위 검사 변수의 절단값은 낮은 민감도로 인해 약시의 진단 기준으로는 한계가 있으며, 진단에 참고할 수 있는 보조적 지표로 활용해 볼 수 있다. <대한안과학회지 2013;54(12):1875-1881> Purpose: To suggest a diagnostic criteria of pattern visual evoked potential (VEP) in adult monocular amblyopic patients in comparison to normal subjects. Methods: The medical records of patients` military service certificates from January 2000 to December 2011 were reviewed. The parameters of pattern VEP were analyzed by comparing monocular amblyopic patients with normal controls. Results: This study included 47 monocular amblyopia and 39 normal control patients. All parameters of pattern VEP were statistically significantly different between monocular amblyopic eyes and normal eyes. The cut-off values for diagnosis of adult amblyopia using receiver operating characteristic (ROC) curve were 113.50 msec (P100 latency), 1.05 (ratio of P100 latency), 8.50 msec (interocular difference of P100 latency), and 5.25 μV (interocular difference of P100 amplitude). Cut-off value sensitivities were generally low: (51.1%, 70.2%, 53.2%, and 31.9%, respectively). Conclusions: The value of pattern VEP parameters had limitations due to low sensitivity and could be considered as ancillary diagnostic criteria when diagnosing amblyopia. J Korean Ophthalmol Soc 2013;54(12):1875-1881